Correlation Between the Concept and Practice of Omission and Positive Fictitious Actions in Government Administration - Muslim, Mutia Jawaz (Department of Constitutional Law, Faculty Sharia and Law, UIN Sunan Ampel Surabaya, 2025)
Regulations concerning government omissions and the concept of positive fiction play a strategic role in the national legal system. These two legal instruments serve to ensure legal certainty, protect the public, and encourage professionalism among state officials in the provision of optimal public services. However, their implementation has raised various questions and issues, especially since the enactment of the Job Creation Law. This study aims to describe the problems that arise due to government inaction and the application of positive fiction in state administration practices. The method used is normative legal research with a conceptual approach and case studies. Through theoretical analysis, court decisions, case studies, and elaboration based on regulations and principles of administrative law, this study finds that government inaction is part of concrete action. These actions are then addressed through the application of the concept of positive fiction as a corrective instrument against the government's failure to fulfill its obligations. However, the issue becomes complex when the authority to resolve disputes related to positive fiction is separated into two different branches of power since the enactment of the Job Creation Law. This separation has the potential to open up opportunities for abuse of process by parties seeking to profit from legal loopholes. Therefore, the authority to review positive fictitious actions should be part of the jurisdiction of the administrative court.